1999
DOI: 10.2355/isijinternational.39.171
|View full text |Cite
|
Sign up to set email alerts
|

Incremental Formulation for the Prediction of Microstructural Change in Multi-pass Hot Forming.

Abstract: A new mathematical formulation for static microstructural changes in hot forming is proposed. This formulation can be easily coupled with incremental modei for dynamic microstructural changes as it is formulated in an incremental form using the dislocation density as a representative variable with the simplification of recrystallized structure.Coupling incremental formulations for dynamic and static microstructural changes, microstructural changesunder multi-pass hot forming are computedand discussed.As these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 2 publications
0
26
0
Order By: Relevance
“…The analytical accuracy of currently used method had been validated earlier, 13,15,16) and it was concluded that this model was accurate enough for predicting the evolution in microstructure in and after hot forming. Table 1 shows the changes of process parameters for the rolling of 127ϫ127 mm square billet down to 12 mm diameter bar, 19) which was given by Maccagno et al Table 1 demonstrates the averages of temperature and strain rate, neglecting their distribution in cross-section and transition in rolling direction.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The analytical accuracy of currently used method had been validated earlier, 13,15,16) and it was concluded that this model was accurate enough for predicting the evolution in microstructure in and after hot forming. Table 1 shows the changes of process parameters for the rolling of 127ϫ127 mm square billet down to 12 mm diameter bar, 19) which was given by Maccagno et al Table 1 demonstrates the averages of temperature and strain rate, neglecting their distribution in cross-section and transition in rolling direction.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows the schematic illustration of integrated analysis. Change in distribution of dislocation density and grain size during hot rolling were analyzed by incremental formulations for microstructure evolution, 12,13) temperature transition and strain rate along each stream line was used as 'process oriented' boundary conditions. Material parameters, embedded in recrystallization kinetics, recoveries etc.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the technique to calculate the change of the internal micro structure depending on the history of stain velocity and rolling temperature was necessary and some techniques were suggested in the 1990s. [124][125][126] In addition, the internal micro structure of material after hot rolling changes while cooling down. The model to analyze the incremental phase transformation for the purpose of the nucleation mechanism in the grain boundary was formulated by Yanagimoto and others, based on the models 127,128) targeted at the plain carbon steel for ferrite, pearlite, and bainite transformation.…”
Section: Expansion Of Application Of the Finite Elementmentioning
confidence: 99%